Improving hydrophilicity of silicone elastomer by IPN formation with hyaluronan - Koch, Richard L., author; James, Susan P., advisor; Bailey, Travis, committee member; Popat, Ketul C., committee member (Colorado State University. Libraries, 2016)
Soft contact lenses have been available to consumers for the past several decades. By far, the most popular form on the market today is the silicone hydrogel, with nearly 70% of the market share. However, many contact lens wearers still have issues which cause them to discontinue lens use. It is estimated that between 25-35% of people discontinue use permanently. This can be traced back to two main issues with modern hydrogel lenses: a lack of adequate oxygen permeability across the lens; and lens-induced dehydration of the cornea. The corneal epithelium lining the lens of the eye is an avascular environment. As such, the cells must get their oxygen by diffusion through the tear film, or any material covering the lens. The silicone hydrogel SCLs have reduced oxygen gas permeability compared to traditional silicone elastomers. Additionally, when the hydrogel lenses lose water to evaporation, they pull water from the wearer's eye, contributing to dryness. Beyond simple discomfort, these issues can lead to pathologies such as hyperemia and even corneal cell death in severe cases. It was determined that a solution to these issues would be a new ocular lens material which had superior oxygen gas permeability and was hydrophilic without containing water in its bulk. The aim of this research was to create an interpenetrating polymer network (IPN) materials of poly(dimethyl siloxane) (PDMS) and hyaluronan (HA) with such properties. The results in this work indicate the successful synthesis of these HA-PDMS IPN materials. These elastomeric materials had improved hydrophilicity compared to untreated PDMS. Additionally, new chemical species (ATR/FTIR and XPS spectroscopy) and surface morphologies (SEM imaging) indicated the introduction of HA into the PDMS. Furthermore, analysis of the oxygen gas permeability showed no significant change for the treated samples as compared to the PDMS base material. As silicone materials have use in many biomedical fields, the material was also tested for platelet adhesion/activation and whole blood clotting. However, studies showed unfavorable results as the treated samples still caused platelet activation and blood clotting. Additionally, overall optical transmittance of the treated materials was significantly decreased. Further refinement of the treatment methods may yield more favorable results in the areas of thrombogenicity and platelet adhesion.
Keywords: interpenetrating polymer network; polymer; surface characterization; poly(dimethyl siloxane); hyaluronan; silicone